2022
DOI: 10.1371/journal.pcbi.1010018
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing and gene sharing network analysis powered by machine learning identifies antibiotic resistance sharing between animals, humans and environment in livestock farming

Abstract: Anthropogenic environments such as those created by intensive farming of livestock, have been proposed to provide ideal selection pressure for the emergence of antimicrobial-resistant Escherichia coli bacteria and antimicrobial resistance genes (ARGs) and spread to humans. Here, we performed a longitudinal study in a large-scale commercial poultry farm in China, collecting E. coli isolates from both farm and slaughterhouse; targeting animals, carcasses, workers and their households and environment. By using wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 107 publications
3
38
0
Order By: Relevance
“…A subset of these samples, 46 chicken faeces samples and 30 human faeces samples, were in common between the present study and Peng et al [24]. Compared with the metagenome data we study here, the whole genome study [24] found stronger evidence of clustering between isolates from different hosts, however, hotspots of similarities were found between samples from livestock and the nose and hands of humans. However, nose and hands were excluded from this study as there were no corresponding metagenome samples.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…A subset of these samples, 46 chicken faeces samples and 30 human faeces samples, were in common between the present study and Peng et al [24]. Compared with the metagenome data we study here, the whole genome study [24] found stronger evidence of clustering between isolates from different hosts, however, hotspots of similarities were found between samples from livestock and the nose and hands of humans. However, nose and hands were excluded from this study as there were no corresponding metagenome samples.…”
Section: Discussionsupporting
confidence: 74%
“…Whilst the gut microbiota is largely commensal and important for health, several studies have found that the microbiota can act as a reservoir for ARGs [16,17], which in other studies have been found to be transferred between livestock and humans [18]. Several studies have found both direct (in food production) [19][20][21][22][23][24][25] and indirect (through food consumption) [26][27][28] evidence of similar antibiotic-resistant bacteria (ARBs) and ARGs between humans and animals/meat. However, the role of farm animals in the emergence and dissemination of ARBs and their resistance determinants to humans is poorly understood and controversial, with some studies comparing samples related on a regional level showing distinct human and animal lineages [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, antigenic shift with reassortment further complicates the evolutionary history. Additionally, there are other cases in which we can quantify similarities but cannot convert these into evolutionary distances, such as gene-sharing networks (14, 15) or protein structure similarity networks (16). Such networks appear not only for studying typical evolution but also for various research into bacterial evolution, including horizontal gene transfer (17) and antibody evolution (18).…”
Section: Introductionmentioning
confidence: 99%